Magnetic measurements in thin film specimens: Rejecting the contribution of the substrate - Manios, E.; Stamopoulos, D.; Moutis, N.; Pissas, M.; Niarchos, D. (JOURNAL OF MAGNETISM AND MAGNETIC MATERIALS, 2008)
We propose a new method for the rejection of the comparatively strong diamagnetic contribution usually observed in SQUID magnetization measurements, originating from the substrates that are widely used for the preparation of thin magnetic films either by sputtering or by laser ablation techniques. Our method relies on the use of a substrate of length exceeding significantly the scan length employed in the magnetization measurements. Simple symmetry considerations reveal that the substrate's signal can be removed efficiently. This is also verified by a simple quantitative model, which is based on the form of total response of the four SQUID pick-up coils for a long sample. Our experimental data show clear evidence that the direct rejection of the substrate's undesired diamagnetic signal is complete in all the different categories of films (CoPt uniform single layers, CoPt isolated nanoparticles and La(1-x)Ca(x)MnO(3) multilayered specimens) studied in the present work. As a result, the real underlying mechanism that governs the physics of these magnetic films was uncovered. (C) 2008 Elsevier B.V. All rights reserved.